2016
DOI: 10.1039/c6cc07143k
|View full text |Cite
|
Sign up to set email alerts
|

A chemical reporter strategy for detecting and identifying O-mycoloylated proteins in Corynebacterium

Abstract: Protein O-mycoloylation is a unique post-translational lipidation that was recently discovered in Corynebacterium. We describe an alkyne-modified trehalose monomycolate chemical reporter that can metabolically tag O-mycoloylated proteins in C. glutamicum, enabling their detection and identification through click chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 32 publications
6
50
0
Order By: Relevance
“…As noted above and depicted in Figure A, TMM reporters have the potential to label both major mycomembrane components, including inner‐leaflet AGM and outer‐leaflet TDM . We previously determined that O‐AlkTMM‐C7 mainly incorporated into the AGM‐containing cellular fraction from Msmeg and less so into the TDM‐containing extractable lipids fraction, which is consistent with AGM being the most abundant mycolate‐containing envelope component . Here, we performed the same cellular fractionation experiments following treatment of Msmeg with 4 – 6 .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…As noted above and depicted in Figure A, TMM reporters have the potential to label both major mycomembrane components, including inner‐leaflet AGM and outer‐leaflet TDM . We previously determined that O‐AlkTMM‐C7 mainly incorporated into the AGM‐containing cellular fraction from Msmeg and less so into the TDM‐containing extractable lipids fraction, which is consistent with AGM being the most abundant mycolate‐containing envelope component . Here, we performed the same cellular fractionation experiments following treatment of Msmeg with 4 – 6 .…”
Section: Resultssupporting
confidence: 63%
“…Cglut encodes six mycoloyltransferases, only one of which, CgMytC, transfers mycoloyl groups from TMM onto polypeptides to generate O‐mycoloylated proteins (Figure A) . Our group previously showed that O‐AlkTMM‐C7 could be used to metabolically label O‐mycoloylated proteins in Cglut with alkyne tags, enabling their subsequent visualization using CuAAC followed by SDS‐PAGE with in‐gel fluorescence analysis . We reasoned that using this experimental platform with a Cglut mutant lacking CgMytC would allow us to assess whether TMM reporters operate in a mycoloyltransferase‐dependent manner, because: 1) CgMytC is not essential; and 2) this system eliminates the issue of mycoloyltransferase redundancy‐again, available evidence suggests that only CgMytC adds O‐mycolates to proteins in Cglut .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azide and alkyne reporters of trehalose have also been developed for two‐step labeling of mycobacteria (Figure F) . Moreover, a TMM chemical reporter has been developed for detection and identification of protein O‐mycoloylation in Corynebacterium (Figure G) . In addition to hexose monosaccharide reporters, several azido‐pentose reporters have been developed to label specific glycans in the mycobacterial cell wall (Figure H) .…”
Section: Chemical Reporters For Microbiologymentioning
confidence: 99%
“…Recently, we also observed that O-AlkTMM can label and facilitate the identification of proteins modified by mycoloyl groups in C. glutamicum . 105 This form of protein post-translational modification (PTM)—termed protein O -mycoloylation—was recently discovered in Corynebacterineae 106,107 but its scope and functional consequences remain unknown. O-AlkTMM will be a useful tool for identifying and characterizing proteins that contain this PTM and for probing the link between protein lipidation and trehalose metabolism in C. glutamicum and related organisms.…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 99%